Merajut Solusi Berkeadilan atas Ketimpangan Politik dan Sosioekonomi Nelayan Kapal Mini Purse Seine di Sarang Rembang - Zaimah, Nely Rahmawati Zaimah; Risty Kamila Wening Estu; Joesidawati, Marita Ika (Wisanggeni: Jurnal Pengabdian Masyarakat, 2025)
This study examines the socio-economic disparity between two groups of coastal fishermen in Sarang, Rembang—those operating freezer-equipped vessels and those using traditional ice-block methods. The research highlights how access to technology and unequal enforcement of local regulations create structural gaps in income, market access, and fiscal contribution. While freezer-equipped fishermen often bypass official auction markets (TPI) and avoid retribution fees, small-scale fishermen are burdened by formal charges, delayed payments, and limited distribution channels. Using a mixed-method approach grounded in distributive justice theory (Rawls) and institutional economics (North), this study combines statistical analysis and field interviews to uncover how unequal access to subsidies and market mechanisms impacts collective welfare. The findings reveal that higher fiscal burdens fall disproportionately on those with fewer resources, weakening trust in cooperatives and local fishery institutions. The study offers critical insight into how structural inequities in marine resource governance can fragment social cohesion and undermine sustainability in traditional fishing communities.